2007
DOI: 10.36253/978-88-8453-465-1
|View full text |Cite
|
Sign up to set email alerts
|

Pictorial Assessment of Interpersonal Relationships (PAIR)

Abstract: Drawing is an invaluable means of expression for children, which has always appealed to psychologists for its direct communicative features, as well as for the possibility of transcending intercultural differences. This volume allows students and researchers to learn a specific methodology of pictorial data analysis. The characteristics of children's drawings of interpersonal relationship, such as friends, siblings, child-parent, are measured by means of six scales: Cohesion, Distancing, Similarity, Value, Emo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 0 publications
0
48
0
Order By: Relevance
“…The Pictorial Assessment of Interpersonal Relationships (PAIR, Bombi et al, 2007) is an analytical system for collecting and coding school‐aged children's and adolescent's representations of their interpersonal relationships. The participants were asked to draw herself or himself with his/her sibling with ASD while they were doing something in (a) a situation of harmony and (b) a situation of conflict.…”
Section: Methodsmentioning
confidence: 99%
“…The Pictorial Assessment of Interpersonal Relationships (PAIR, Bombi et al, 2007) is an analytical system for collecting and coding school‐aged children's and adolescent's representations of their interpersonal relationships. The participants were asked to draw herself or himself with his/her sibling with ASD while they were doing something in (a) a situation of harmony and (b) a situation of conflict.…”
Section: Methodsmentioning
confidence: 99%
“…The PAIR (Bombi et al, 2007) analysis method was used to meet the aim of exploring hospitalized children’s views of their relationships with nurses and doctors. The PAIR is a system of analysing drawings, developed by an Italian research group in the 1990s, with the aim of studying the representations that school-age children make of their interpersonal relationships.…”
Section: Methodsmentioning
confidence: 99%
“…In particular it has been used to investigate friendship, relationships with parents and relationships with teachers. Several studies (Bombi et al, 2007) have shown that the instrument has construct validity (a theoretical analysis on the relevance of each dimension to the study of friendship and other relationships was conducted), reliability (agreement range from 96% to 99%) and discriminant validity (a main effect of the type of drawing – friend vs non-friend – emerged in all the four scales in a study with 100 Italian children aged between 6 and 11 years). The task consisted of creating a picture.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pinto and Di Prospero (2000) asked 100 children (age 6 to 10 years) to produce two drawings, one of "harmony" and one of "disharmony" between themselves and one of their teachers. The authors scored the drawings with PAIR (Bombi et al, 2007), a method of analysis devoted to measure various qualities of depicted interpersonal relationships. Pinto and Di Prospero (2000) found a significant difference between drawings in terms of a higher number of pictorial indices of psychological distance in disharmony situations, possibly indicating a defensive need for a larger personal space.…”
Section: Article In Pressmentioning
confidence: 99%